Jane Eyre de Michael Berkeley et de David Malouf : La transposition opératique d’un grand classique de la littérature anglaise - Jean-Philippe Heberlé (Revue LISA)
This article discusses Michael Berkeley’s opera Jane Eyre. Premiered on June 30, 2000 by Music Theatre Wales at the Cheltenham International Festival of Music, this opera is based on the novel by Charlotte Brontë and the libretto is written by the Australian poet, novelist, playwright and librettist, David Malouf. It was risky and daring to try to adapt this famous and long novel for the stage. We will particularly focus on the similarities and differences between the novel and the opera as well as on the strategies used both by David Malouf and Michael Berkeley to adapt it. Through the analysis of the similarities we will see how Michael Berkeley set to music some of the great themes and elements of the novel: passion, a sense of entrapment, the “Gothic” atmosphere. On the other hand, the analysis of the discrepancies between the novel and the opera as they appear in both the libretto and the music will lead us to a modern apprehension of the characterization of madness as well as of the metafictional dimension of the rewriting of Jane Eyre by David Malouf and Michael Berkeley.